2020
DOI: 10.1097/brs.0000000000003445
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Management Trends of Metastatic Spinal Tumors in South Korea

Abstract: Study Design. Population-based study. From 2008 to 2017, data from the national database of the Korean Health Insurance Review & Assessment Service were analyzed. The national insurance system and all medical expense bill data of the entire population are included in the database. Objective. The aim of this study was to elucidate the incidence and management trends of metastatic spinal tumors in South Korea. Summary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This is also supported by the fact that our study demonstrated a trend towards less invasive methods of surgical management in the treatment of spinal metastases by demonstrating a decrease in the rate of gross total tumor removal. This is also supported by the study performed by Choi et al 34) who reported a decreasing trend towards vertebrectomy and an increasing frequency of resection and instrumentation surgeries. This is largely made possible by advancements in systemic and stereotactic radiotherapy.…”
Section: Discussionsupporting
confidence: 75%
“…This is also supported by the fact that our study demonstrated a trend towards less invasive methods of surgical management in the treatment of spinal metastases by demonstrating a decrease in the rate of gross total tumor removal. This is also supported by the study performed by Choi et al 34) who reported a decreasing trend towards vertebrectomy and an increasing frequency of resection and instrumentation surgeries. This is largely made possible by advancements in systemic and stereotactic radiotherapy.…”
Section: Discussionsupporting
confidence: 75%
“…There is a growing interest in managing SMs because of their crucial clinical implications in oncological patients and their consequent increasing social and economic burden ( 21 ). The spine represent the most common localization of bone metastasis, accounting for about 50% of all the secondary malignant growths ( 22 , 23 ). Moreover, up to 20% of these patients will experience metastatic spinal cord compression (MSCC).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more conservative treatments have been given in the past. In recent years, advances in radiation therapy and systemic antitumor drugs, such as stereotactic body radiotherapy (SBRT), target therapies, and immunological therapies have demonstrated encouraging therapeutic outcomes and have largely expanded the survival time of patients with SMLC [5][6][7][8][9][10][11]. At the same time, surgical treatment has been widely accepted for some SMLC cases [12].…”
Section: Introductionmentioning
confidence: 99%